Robot‐assisted spleen preserving pancreatic surgery in MEN1 patients. Issue 4 (6th June 2016) - Nell, Sjoerd; Brunaud, Laurent; Ayav, Ahmet; Bonsing, Bert A.; Groot Koerkamp, Bas; Nieveen van Dijkum, Els J.; Kazemier, Geert; de Kleine, Ruben H.J.; Hagendoorn, Jeroen; Molenaar, I. Quintus; Valk, Gerlof D.; ,; et al.
Abstract : Background: Multiple Endocrine Neoplasia type 1 (MEN1) patients often undergo multiple pancreatic operations at a young age. Objective: To describe robot‐assisted and laparoscopic spleen‐preserving pancreatic surgery in MEN1 patients, and to compare both techniques. Methods: Robot‐assisted pancreatectomies of the DutchMEN1 study group and the Université de Lorraine, Nancy, France were compared to a historical cohort of laparoscopic treated MEN1 patients. Perioperative outcomes were compared. Results: A total of 21 MEN1 patients underwent minimally invasive pancreatic surgery for pancreatic neuroendocrine tumors, seven patients were subjected to robot‐assisted surgery, and 14 patients underwent laparoscopic surgery. Demographics and clinical characteristics did not differ between the cohorts and no significant differences in operative outcomes were found. A high number of ISGPS grade B/C pancreatic fistulas were observed in both cohorts (38%), and no conversions were seen in the robot‐assisted cohort (respectively 0% vs. 43%, P = 0.06). In one laparoscopic and one robot‐assisted case the primary tumor was not resected. Conclusions: Minimally invasive spleen‐preserving surgery in MEN1 patients is safe and feasible. Patients who underwent robot‐assisted surgery did not require conversion to open surgery. J. Surg. Oncol. 2016;114:456–461 . © 2016 Wiley Periodicals, Inc.